Глобальні виклики та міжнародні відносини у сфері миру та безпеки - Волоснікова, Наталія Миколаївна; Абрамов, Федір Володимирович; Яцина, Вікторія Валентинівна (Національний технічний університет "Харківський політехнічний інститут", 2025)
Стаття присвячена аналізу глобальних викликів у контексті міжнародних відносин у сфері миру та безпеки, зокрема з урахуванням сучасних геополітичних та соціально-економічних трансформацій. Автори досліджують вплив глобальних викликів на функціонування міжнародної безпеки, зокрема акцентуючи увагу на зміні пріоритетів міжнародних організацій у відповіді на новітні загрози, що постають перед світовим співтовариством. Особливу увагу приділено ролі міжнародних організацій, таких як Організація Об'єднаних Націй, Європейський Союз, НАТО, а також неурядових організацій у формуванні стратегії миротворчості, превентивної дипломатії та гуманітарної допомоги в умовах збройних конфліктів. У статті також детально аналізується вплив війни в Україні на міжнародні відносини та механізми забезпечення безпеки на глобальному та регіональному рівнях. Привернута увага до важливості ефективної координації міжнародних зусиль у сфері підтримки суверенітету держави, захисту прав людини та забезпечення мирного врегулювання конфліктів. В умовах війни в Україні міжнародні організації відіграють важливу роль у забезпеченні гуманітарної допомоги, контролю за дотриманням міжнародного права та сприянні процесу примирення. Розглядаються можливості для розвитку нових моделей міжнародної співпраці, що враховують потреби держав, які опинилися в умовах збройних конфліктів, а також важливість міжнародної солідарності у забезпеченні стабільності та безпеки в глобальному вимірі. Стаття підкреслює, що ефективне реагування на глобальні виклики вимагає від міжнародних організацій швидкої адаптації до нових умов, розвитку нових форм співпраці, а також покращення механізмів реагування на загрози, що виникають у світовій політиці. Оцінка ролі міжнародних організацій у сучасному світі дозволяє створити більш точне уявлення про їх місце та роль у формуванні нової системи міжнародних відносин, де взаємодія між державами та міжнародними інститутами стає ключовою умовою для забезпечення миру та безпеки.

This article focuses on the analysis of global challenges in the context of international relations, particularly in the areas of peace and security, considering current geopolitical and socio-economic transformations. The authors explore the impact of global challenges on the functioning of international security, with a special emphasis on the evolving priorities of international organizations in responding to emerging threats faced by the international community. The role of international organizations, such as the United Nations, the European Union, NATO, and non-governmental organizations, in shaping strategies for peacebuilding, preventive diplomacy, and humanitarian aid in the face of armed conflicts is critically examined. The article also provides a detailed analysis of the ongoing war in Ukraine and its implications for international relations and security mechanisms at both global and regional levels. Attention is drawn to the importance of effective international cooperation in supporting state sovereignty, protecting human rights, and ensuring peaceful conflict resolution. Amid the war in Ukraine, international organizations play a crucial role in providing humanitarian assistance, monitoring compliance with international law, and facilitating reconciliation processes. The article explores the potential for developing new models of international cooperation that address the needs of countries embroiled in armed conflicts, highlighting the importance of international solidarity in ensuring global stability and security. Furthermore, the study emphasizes that responding effectively to global challenges requires international organizations to adapt swiftly to new circumstances, develop innovative forms of collaboration, and improve mechanisms for addressing emerging threats in global politics. The assessment of the role of international organizations in the contemporary world enables a more precise understanding of their place and function in shaping a new system of international relations, where the interaction between states and international institutions becomes a key condition for maintaining peace and security. In light of the ongoing geopolitical crises, including the war in Ukraine, the article advocates for a reevaluation of the international security architecture, proposing concrete measures for enhancing global peacekeeping efforts. It stresses the need for further strengthening multilateral frameworks and improving the coordination of actions to tackle shared global security concerns such as terrorism, climate change, and the proliferation of weapons.
Logistics synergy and security system for sustainable development in global hazards
Keywords: глобальні виклики; міжнародні відносини; мир і безпека; міжнародні організації; гуманітарна допомога; збройні конфлікти; міжнародне право; global challenges; international relations; peace and security; international organizations; humanitarian aid; armed conflicts; international law; multilateralism; global peacekeeping